Research status and perspective on recurrent IgA nephropathy after kidney transplantation - Zhang Shu-yu; Li Yue-hong (Linchuang shenzangbing zazhi, 2025)
IgA nephropathy （IgAN） is the most common primary glomerular disease in the world. For patients with end-stage renal disease caused by IgAN， kidney transplantation is one of the most effective options. The annual recurrence rate of IgAN after transplantation varies from 1% to 10%， according to the follow-up time， diagnostic method， and renal biopsy criteria. IgAN recurrence is an important cause of allograft failure. This review aims to summarize the incidence， pathogenesis， risk factors， diagnosis， treatment strategies， and future prospects of recurrent IgAN after renal transplantation.